IMPLEMENTATION OF OFFICIAL MANUSCRIPTS AT REGIONAL FINANCE AND ASSETS AGENCY NORTH SULAWESI PROVINCE - Tumbel, Goinpeace; Masengi, Evi; Jacop, Frilly (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2023)
This research aims to identify and describe the implementation of official scripts in regional financial and wealth management bodies in North Sulawesi Province. The research method used is descriptive qualitative. This research aims to identify and describe the process of arranging official documents carried out at BKAD as well as identifying and describing obstacles in the process of arranging official documents carried out at BKAD based on applicable regulations or SOPs. The second is Supervision, in the implementation of official documents in the regional financial and heritage management bodies of North Sulawesi province it has been covered. And thirdly, the behavior of implementers, regarding the implementation of official scripts in the regional financial and heritage management agency of North Sulawesi province, is still very lacking, the routine in managing messages is still the same.